Divergent beliefs about food safety and affordability in Nigeria - Liverpool-Tasie, L.S.O.; Wineman, A.; Resnick, Danielle (Elsevier, 2024)
Access to safe, affordable diets is paramount for improved nutritional outcomes. Yet, how do stakeholders perceive the binding constraints and requisite policy actions to increase food safety and affordability? Focusing on Nigeria, this paper uses best-worst scaling techniques applied to a survey of 200 government and agrifood system stakeholders to examine their policy beliefs on safety and affordability vis-`a-vis the vegetable and fish value chains. We find that divergence among stakeholders is greater for food safety than affordability. While antibiotics overuse and toxin exposure, lack of knowledge, and weak legislation were identified by different stakeholders as the binding constraints for food safety, high costs of inputs and infrastructure, as well as security threats, were seen as common challenges for affordability across most, though not all, stakeholders for both value chains. Overall, the paper highlights the importance of beliefs in the agrifood system policymaking process and emphasizes the need to explore not only the existence but also the source of divergent beliefs among policy actors in greater depth.